Air electrode catalyst and preparation method thereof, air electrode treatment method and zinc-air battery device
Through the application of alkali treatment of loofah and the application of urea additives in thermal decomposition reactions, an air electrode catalyst with high adsorption uniformity and metal-carbon bond firmness was prepared, which solved the problem of insufficient activity and stability of the zinc-air battery catalyst and significantly improved the charging and discharge performance of the battery.
Patent Information
- Application Number
- CN202411768554.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The discharge voltage, current and capacity of zinc-air batteries are limited, and the adsorption uniformity of the catalyst and the firmness of the metal-carbon bond are poor, resulting in poor activity, conductivity and stability of the catalyst.
The air electrode catalyst is prepared by alkali treatment of loofah, preparation of aerogel precursors and thermal decomposition reaction. The hydrophilicity of loofah is enhanced by alkali treatment, and NH3 and water vapor are released in the thermal decomposition reaction using urea to form nitrogen-doped carbon materials, and metal ions are evenly absorbed through metal salt soaking.
It improves the adsorption uniformity of metal ions and the firmness of metal-carbon bonds, enhances the conductivity and stability of the catalyst, and improves the charge and discharge cycle performance and rate performance of zinc-air batteries.
Smart Images

Figure CN119601678A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts and metal-air batteries, and in particular to an air electrode catalyst and a preparation method thereof, an air electrode treatment method and a zinc-air battery device. Background Art
[0003] Some highly integrated smart grids and electric vehicle industries have begun to develop rapidly. Therefore, electrochemical energy storage and conversion have become an important part of the development of new green energy. Among them, metal-air batteries powered by metal oxidation and oxygen reduction have the advantages of high energy density, low cost and environmental friendliness, and are considered to be the next generation of clean energy. In metal-air batteries, commonly used metal electrodes include zinc and aluminum, among which the reserves of metallic zinc on the earth are about 300 times that of metallic lithium, and zinc has strong corrosion resistance in alkaline solutions, making zinc-air batteries one of the promising battery systems. In addition, the theoretical energy density of zinc-air batteries is as high as 1350Wh kg-1, which is about 5 times that of lithium-ion batteries, but its cost is much lower than that of lithium-ion batteries, showing superior eco-friendliness and high safety. Based on the above advantages, zinc-air batteries have great potential to become a new generation of electrochemical energy storage devices.
[0004] At present, zinc-air batteries are still in the early stages of research and development, and the following bottlenecks remain to be overcome: (1) The discharge voltage, current and capacity of a single zinc-air battery are limited, and the charge and discharge performance and rate performance are insufficient to meet the needs of large-scale applications, resulting in low charge and discharge efficiency. (2) The catalyst used in zinc-air batteries has poor uniformity in adsorption of metal ions, and the metal-carbon bond is not strong enough. The distribution uniformity of the catalyst in the electrode is also poor, resulting in poor activity, conductivity and stability of the catalyst. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing an air electrode catalyst, which can improve the adsorption uniformity of metal ions and make the formed metal-carbon bond stronger, and has the advantages of good conductivity and stability.
[0006] In order to overcome the deficiencies of the prior art, the second object of the present invention is to provide an air electrode catalyst having the advantages of good uniformity of metal ion adsorption, good firmness of metal-carbon bonds, good conductivity and stability.
[0007] The third object of the present invention is to provide an air electrode processing method, which can ensure that the catalyst is evenly distributed on the air electrode, thereby ensuring the activity of the catalyst, and the catalyst is not easy to fall off the air electrode, thereby ensuring the stability of the air electrode during operation.
[0008] The fourth object of the present invention is to provide a zinc-air battery device, which has excellent charge and discharge cycle performance and rate performance, and the battery has high charge and discharge efficiency, is easy to install, and can avoid leakage problems.
[0009] In order to achieve the first object of the above invention, the technical solution adopted by the present invention is as follows:
[0010] The present invention provides a method for preparing an air electrode catalyst, comprising the following steps:
[0011] S1, alkali treatment of loofah: dispersing the loofah in an alkali solution, then heating it for hydrothermal reaction, vacuum filtering, washing and drying to obtain an alkali-treated loofah;
[0012] S2. Preparation of an aerogel precursor: soaking the alkali-treated loofah in a mixed aqueous solution containing cobalt ions, iron ions and urea, stirring and freeze-drying the mixture to obtain an aerogel precursor;
[0013] S3, thermal decomposition reaction: subjecting the aerogel precursor to thermal decomposition reaction under a protective atmosphere to obtain the air electrode catalyst.
[0014] The invention discloses a method for preparing an air electrode catalyst. First, the cell wall structure of the loofah is disintegrated after being treated with an alkaline solution, and the lignin and hemicellulose are dissolved in the alkaline solution, thereby obtaining a cellulose dispersion. After filtration, washing and drying, the loofah is converted into cellulose with good hydrophilicity, which greatly enhances the hydrophilicity of the loofah and is beneficial to the adsorption of metal ions in the subsequent preparation of an aerogel precursor. In the preparation of the aerogel precursor, urea is also added to the mixed aqueous solution containing cobalt ions and iron ions. Urea will decompose and release NH3 and water vapor at high temperature in the subsequent thermal decomposition reaction, and NH3 can be used as a source gas for nitrogen doping to incorporate nitrogen atoms into the thermally decomposed carbon substrate; in addition, urea also acts as a reducing agent to reduce the oxidized carbon material to a carbon material, thereby improving the conductivity of the carbon material.
[0015] In addition, in the preparation method of the air electrode catalyst, the following advantages are achieved by first immersing the alkali-treated loofah in a metal salt and then carbonizing it: 1) immersing it in a metal salt before carbonization can make the cobalt ions and iron ions uniformly adsorbed on the surface of the biomass or penetrate into the interior thereof, and in the subsequent carbonization process of the thermal decomposition reaction, the metal can be more evenly distributed in the carbon material; 2) the metal ions interact with the organic components in the biomass or aerogel precursor during the carbonization process of the thermal decomposition reaction to form a stronger metal-carbon bond, thereby improving the stability and performance of the air electrode catalyst.
[0016] Furthermore, in step S1, the loofah is dispersed in an alkaline solution, and then heated to 140°C-160°C for hydrothermal reaction for 10h-14h, and then vacuum filtered, washed with deionized water until neutral, and placed in a vacuum drying oven at 50°C-70°C for 10h-20h to obtain an alkali-treated loofah; and / or
[0017] The alkaline solution is one or both of potassium hydroxide and sodium hydroxide; the molar concentration of the alkaline solution is 2M-4M; and / or
[0018] The mass ratio of the loofah to the alkaline solution is 1:(8-12).
[0019] Furthermore, in step S2, the alkali-treated loofah is immersed in a mixed aqueous solution containing Co(NO3)2·6H2O, Fe(NO3)3·9H2O and urea, and magnetically stirred for 50 min-70 min, and then freeze-dried with liquid nitrogen for 45 h-50 h to obtain an aerogel precursor; and / or
[0020] The molar concentrations of the cobalt ions and the iron ions are both 0.05mM-0.15mM, the molar concentration of the urea is 1M-1.5M, and the mass ratio of the alkali-treated loofah to the mixed aqueous solution is 1:(45-55).
[0021] Furthermore, in step S3, the aerogel precursor is placed in a tubular furnace, heated to 850°C-950°C at a heating rate of 4°C / min-6°C / min in an argon atmosphere, and subjected to thermal decomposition reaction for 1.5h-2.5h to obtain the air electrode catalyst.
[0022] In order to achieve the second purpose of the above invention, the technical solution adopted by the present invention is as follows:
[0023] The present invention provides an air electrode catalyst, which is prepared by the above-mentioned preparation method of the air electrode catalyst.
[0024] In order to achieve the third purpose of the above invention, the technical solution adopted by the present invention is as follows:
[0025] The present invention provides an air electrode treatment method, which is a method for treating an air electrode using an air electrode catalyst prepared by the above-mentioned method for preparing an air electrode catalyst, comprising the following steps:
[0026] 1) Preparation of catalyst ink: placing the air electrode catalyst and conductive carbon black in a container, adding water, anhydrous ethanol and Nafion solution, and then performing ultrasonic dispersion to prepare catalyst ink;
[0027] 2) Forming a catalyst layer on the current collector: under the irradiation of an infrared lamp, the catalyst ink is dripped onto the current collector that has been meshed with the air diffusion layer, and after the current collector is left to stand under the infrared lamp, the air electrode treatment is completed.
[0028] The present invention provides an air electrode processing method, through the combination of air electrode catalyst and conductive carbon black, conductive carbon black helps the transmission of electrons in the electrode, the air electrode catalyst can promote the reduction reaction of oxygen on the electrode surface, thereby improving the catalytic activity and conductivity of the air electrode. In addition, by dispersing the air electrode catalyst and conductive carbon black in a mixture of water, anhydrous ethanol and Nafion solution, and uniformly dispersing them through ultrasonic treatment to form an ink-like suspension, it is possible to ensure that the air electrode catalyst is evenly distributed on the electrode, thereby ensuring the activity of the catalyst. In addition, by dropping the catalyst ink onto the current collector that has been meshed with the air diffusion layer, and leaving it to dry under an infrared lamp, the catalyst ink can be firmly attached to the current collector to form a catalyst layer, ensuring that the catalyst is not easy to fall off on the air electrode, thereby improving the stability of the air electrode during operation.
[0029] Furthermore, in the preparation step of the catalyst ink, the mass volume ratio of the air electrode catalyst, conductive carbon black, water, anhydrous ethanol and Nafion solution is (3-4) mg: (1-2) mg: (450-500) μL: (450-500) μL: (40-60) μL; and / or, the conductive carbon black is Ketjen black; and / or, the water is ultrapure water; and / or, the ultrasonic dispersion is ultrasonically dispersed in an ultrasonic cleaning machine for 50 min-70 min.
[0030] Furthermore, in the step of forming the catalyst layer on the current collector, the catalyst ink is dripped onto the current collector which has been meshed with the waterproof breathable membrane under the irradiation of an infrared lamp at 75°C-85°C, and the air electrode treatment is completed after standing under the infrared lamp for 20min-40min.
[0031] Further, the air diffusion layer is a waterproof breathable membrane; and / or the thickness of the waterproof breathable membrane is 0.1 mm-0.3 mm, and the porosity of the waterproof breathable membrane is 15%-30%; and / or
[0032] The current collector is one of stainless steel mesh, nickel foam, carbon paper or carbon cloth.
[0033] In order to achieve the fourth object of the above invention, the technical solution adopted by the present invention is as follows:
[0034] The present invention provides a zinc-air battery device, comprising at least one battery cell, wherein the battery cell comprises a zinc electrode and an air electrode treated by the air electrode treatment method described above.
[0035] Furthermore, the battery unit also includes an electrode plate, a fixed ventilation plate, and a fixed pressure plate;
[0036] The zinc electrode and the air electrode are arranged opposite to each other, the electrode plate is arranged between the zinc electrode and the air electrode, the fixed ventilation plate is arranged on the other side of the air electrode, and the fixed pressure plate is arranged on the other side of the zinc electrode;
[0037] The electrode plate is provided with an electrolyte tank, in which an electrolyte is provided;
[0038] An air inlet penetrating through the fixed ventilation plate is provided in the middle of the fixed ventilation plate; and / or
[0039] Gaskets are arranged between the air electrode and the electrode plate, and between the zinc electrode and the electrode plate.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) A method for preparing an air electrode catalyst of the present invention includes alkali treatment of loofah, preparation of an aerogel precursor and thermal decomposition reaction. The use of alkali solution to treat the loofah can enhance the hydrophilicity of the loofah, which is beneficial to the adsorption of metal ions in the subsequent preparation of the aerogel precursor. In the preparation of the aerogel precursor, urea is also added to the mixed aqueous solution containing cobalt ions and iron ions. On the one hand, NH3 released by urea after thermal decomposition reaction can be used as a source gas for nitrogen doping, and nitrogen atoms are incorporated into the thermally decomposed carbon substrate, thereby improving the catalytic activity of the air electrode catalyst in the oxygen reduction reaction. On the other hand, in addition, urea also acts as a reducing agent to reduce the oxidized carbon material to a carbon material, thereby improving the conductivity of the carbon material.
[0042] (2) A method for preparing an air electrode catalyst of the present invention, by first immersing an alkali-treated loofah in a metal salt and then carbonizing it, can make cobalt ions and iron ions uniformly adsorbed on the surface of biomass or penetrate into it, and in the subsequent carbonization process of thermal decomposition reaction, the metal can be more evenly distributed in the carbon material. In addition, the metal ions interact with the organic components in the biomass or aerogel precursor during the carbonization process of the thermal decomposition reaction to form a stronger metal-carbon bond, thereby improving the stability and electrocatalytic activity of the air electrode catalyst.
[0043] (3) The air electrode catalyst of the present invention has excellent catalytic activity and conductivity, the metal is well distributed in the carbon material, and the metal-carbon bond is strong. Therefore, the air electrode catalyst has good stability.
[0044] (4) The present invention provides an air electrode treatment method, which combines an air electrode catalyst with conductive carbon black. The conductive carbon black helps the transmission of electrons in the electrode, and the air electrode catalyst can promote the reduction reaction of oxygen on the electrode surface, thereby improving the catalytic activity and conductivity of the air electrode. In addition, by dispersing the air electrode catalyst and the conductive carbon black in a mixture of water, anhydrous ethanol and Nafion solution, and uniformly dispersing them through ultrasonic treatment to form an ink-like suspension, it is possible to ensure that the air electrode catalyst is evenly distributed on the electrode, thereby ensuring the activity of the catalyst. In addition, by dropping the catalyst ink onto the current collector that has been meshed with the air diffusion layer, and leaving it to dry under an infrared lamp, the catalyst ink can be firmly attached to the current collector to form a catalyst layer, ensuring that the catalyst is not easy to fall off on the air electrode, thereby improving the stability of the air electrode during operation.
[0045] (5) A zinc-air battery device of the present invention comprises at least one battery cell, wherein the battery cell comprises a zinc electrode and an air electrode treated by an air electrode treatment method. Compared with precious metal catalysts, the zinc-air battery device has excellent charge and discharge cycle performance and rate performance, and the battery has high charge and discharge efficiency, is easy to install, and can avoid leakage. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 It is a TEM image of the air electrode catalyst (FeCo@NC-900) prepared in Example 1 of the present invention.
[0048] Figure 2 It is the H-TEM image of the air electrode catalyst (FeCo@NC-900) prepared in Example 1 of the present invention.
[0049] Figure 3 TEM image showing the lattice fringes of FeCo alloy particles in the air electrode catalyst (FeCo@NC-900) prepared in Example 1 of the present invention.
[0050] Figure 4 It is a TEM image showing the lattice fringes of the outer graphitized carbon layer in the air electrode catalyst (FeCo@NC-900) prepared in Example 1 of the present invention.
[0051] Figure 5 This is a graph showing the particle size distribution test results of the air electrode catalyst prepared in Example 1 of the present invention.
[0052] Figure 6 It is the XRD diagram of the air electrode catalyst (FeCo@NC-900) prepared in Example 1 of the present invention.
[0053] Figure 7 3 is a graph showing the ORR activity test results of the air electrode catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0054] Figure 8 1 is a graph showing the OER activity test results of the air electrode catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0055] Fig. 9 3 is a graph showing the ORR activity test results of the air electrode catalysts prepared in Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5.
[0056] Fig.10 It is a graph showing the OER activity test results of the air electrode catalysts prepared in Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5.
[0057] Fig.11 The graphs are the results of constant current charge and discharge tests on the zinc-air battery devices of Example 12 and Comparative Example 6.
[0058] Fig.12 It is a schematic structural diagram of a zinc-air battery device according to Example 12 of the present invention.
[0059] Fig.13 It is a schematic cross-sectional structural diagram of a zinc-air battery device according to Example 12 of the present invention.
[0060] Fig.14 It is a schematic structural diagram of a zinc-air battery device according to Example 13 of the present invention.
[0061] The reference numerals are as follows:
[0062] Zinc electrode 1; air electrode 2, current collector 21, air diffusion layer 22, catalyst layer 23; electrode plate 3, electrolyte tank 31, electrolyte injection port 32; fixed ventilation plate 4, air inlet 41; fixed pressure plate 5; gasket 6; bolt hole 7. DETAILED DESCRIPTION
[0063] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0064] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. In the present invention, the singular forms "a", "said" and "the" used in the embodiments and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0065] The following describes the invention in conjunction with specific embodiments.
[0066] Example 1
[0067] A method for preparing an air electrode catalyst comprises the following steps:
[0068] S1. Alkali treatment of loofah: The loofah was dispersed in a potassium hydroxide solution with a molar concentration of 3M, and then heated to 150°C for hydrothermal reaction for 12 hours, and then vacuum filtered, washed with deionized water until neutral, and placed in a vacuum drying oven at 60°C for 15 hours to obtain an alkali-treated loofah; in this embodiment, the mass ratio of loofah to potassium hydroxide is 1:10;
[0069] S2. Preparation of aerogel precursor: Soak the alkali-treated loofah in a mixed aqueous solution containing Co(NO3)2·6H2O, Fe(NO3)3·9H2O and urea, and perform magnetic stirring for 60 minutes, and then freeze-dry with liquid nitrogen for 48 hours to obtain an aerogel precursor; in this embodiment, the molar concentration of cobalt ions is 0.1mM, the molar concentration of iron ions is 0.1mM, the molar concentration of urea is 1.2M, and the mass ratio of the alkali-treated loofah to the mixed aqueous solution is 1:50;
[0070] S3. Thermal decomposition reaction: The aerogel precursor was placed in a tubular furnace, heated to 900°C at a heating rate of 5°C / min under an argon atmosphere for a thermal decomposition reaction for 2 hours to obtain an air electrode catalyst (denoted as FeCo@NC-900).
[0071] Example 2
[0072] A method for preparing an air electrode catalyst comprises the following steps:
[0073] S1. Alkali treatment of loofah: The loofah was dispersed in a sodium hydroxide solution with a molar concentration of 2M, and then heated to 140°C for hydrothermal reaction for 14 hours, and then vacuum filtered, washed with deionized water until neutral, and placed in a vacuum drying oven at 50°C for 20 hours to obtain an alkali-treated loofah; in this embodiment, the mass ratio of loofah to sodium hydroxide is 1:8;
[0074] S2. Preparation of aerogel precursor: Soak the alkali-treated loofah in a mixed aqueous solution containing Co(NO3)2·6H2O, Fe(NO3)3·9H2O and urea, and perform magnetic stirring for 50 minutes, and then freeze-dry with liquid nitrogen for 45 hours to obtain an aerogel precursor; in this embodiment, the molar concentration of cobalt ions is 0.05mM, the molar concentration of iron ions is 0.05mM, the molar concentration of urea is 1M, and the mass ratio of the alkali-treated loofah to the mixed aqueous solution is 1:45;
[0075] S3. Thermal decomposition reaction: The aerogel precursor is placed in a tubular furnace, and heated to 850°C at a heating rate of 4°C / min under an argon atmosphere for a thermal decomposition reaction for 2.5 hours to obtain an air electrode catalyst.
[0076] Example 3
[0077] A method for preparing an air electrode catalyst comprises the following steps:
[0078] S1. Alkali treatment of loofah: The loofah was dispersed in a potassium hydroxide solution with a molar concentration of 4M, and then heated to 160°C for hydrothermal reaction for 10 hours, and then vacuum filtered, washed with deionized water until neutral, and dried in a vacuum drying oven at 70°C for 10 hours to obtain an alkali-treated loofah; in this embodiment, the mass ratio of loofah to potassium hydroxide is 1:12;
[0079] S2. Preparation of aerogel precursor: Soak the alkali-treated loofah in a mixed aqueous solution containing Co(NO3)2·6H2O, Fe(NO3)3·9H2O and urea, and perform magnetic stirring for 70 minutes, and then freeze-dry with liquid nitrogen for 50 hours to obtain an aerogel precursor; in this embodiment, the molar concentration of cobalt ions is 0.15mM, the molar concentration of iron ions is 0.15mM, the molar concentration of urea is 1.5M, and the mass ratio of the alkali-treated loofah to the mixed aqueous solution is 1:55;
[0080] S3. Thermal decomposition reaction: The aerogel precursor is placed in a tubular furnace, and heated to 950°C at a heating rate of 6°C / min under an argon atmosphere for a thermal decomposition reaction for 1.5 hours to obtain an air electrode catalyst.
[0081] Example 4
[0082] A method for preparing an air electrode catalyst comprises the following steps:
[0083] S1. Alkali treatment of loofah: The loofah was dispersed in a potassium hydroxide solution with a molar concentration of 2.5 M, and then heated to 145° C. for hydrothermal reaction for 13 h, and then vacuum filtered, washed with deionized water until neutral, and dried in a vacuum drying oven at 55° C. for 18 h to obtain an alkali-treated loofah; in this embodiment, the mass ratio of loofah to potassium hydroxide is 1:9;
[0084] S2. Preparation of aerogel precursor: Soak the alkali-treated loofah in a mixed aqueous solution containing Co(NO3)2·6H2O, Fe(NO3)3·9H2O and urea, and perform magnetic stirring for 55 minutes, and then freeze-dry with liquid nitrogen for 46 hours to obtain an aerogel precursor; in this embodiment, the molar concentration of cobalt ions is 0.08mM, the molar concentration of iron ions is 0.12mM, the molar concentration of urea is 1.1M, and the mass ratio of the alkali-treated loofah to the mixed aqueous solution is 1:48;
[0085] S3. Thermal decomposition reaction: The aerogel precursor is placed in a tubular furnace, and heated to 880°C at a heating rate of 5°C / min under an argon atmosphere for a thermal decomposition reaction for 2.2 hours to obtain an air electrode catalyst.
[0086] Example 5
[0087] A method for preparing an air electrode catalyst comprises the following steps:
[0088] S1. Alkali treatment of loofah: The loofah was dispersed in a sodium hydroxide solution with a molar concentration of 3.5 M, and then heated to 155° C. for hydrothermal reaction for 11 h, vacuum filtered, washed with deionized water until neutral, and dried in a vacuum drying oven at 65° C. for 12 h to obtain an alkali-treated loofah; in this embodiment, the mass ratio of loofah to sodium hydroxide is 1:11;
[0089] S2. Preparation of aerogel precursor: Soak the alkali-treated loofah in a mixed aqueous solution containing Co(NO3)2·6H2O, Fe(NO3)3·9H2O and urea, and perform magnetic stirring for 65 minutes, and then freeze-dry with liquid nitrogen for 49 hours to obtain an aerogel precursor; in this embodiment, the molar concentration of cobalt ions is 0.13mM, the molar concentration of iron ions is 0.07mM, the molar concentration of urea is 1.4M, and the mass ratio of the alkali-treated loofah to the mixed aqueous solution is 1:52;
[0090] S3. Thermal decomposition reaction: The aerogel precursor is placed in a tubular furnace, and heated to 920°C at a heating rate of 4°C / min under an argon atmosphere for a thermal decomposition reaction for 1.8 hours to obtain an air electrode catalyst.
[0091] Example 6
[0092] A method for treating an air electrode is a method for treating an air electrode using an air electrode catalyst prepared by the method for preparing an air electrode catalyst in Example 1, comprising the following steps:
[0093] 1) Preparation of catalyst ink: air electrode catalyst and Ketjen black are placed in a container, and ultrapure water, anhydrous ethanol and Nafion solution are added, and then ultrasonically dispersed in an ultrasonic cleaning machine for 60 minutes to prepare catalyst ink; in this embodiment, the mass volume ratio of air electrode catalyst, conductive carbon black, water, anhydrous ethanol and Nafion solution is 3.5 mg: 1.5 mg: 475 μL: 475 μL: 50 μL;
[0094] 2) Forming a catalyst layer on the current collector: Under irradiation with an infrared lamp at 80°C, drop catalyst ink onto the current collector that has been meshed with a waterproof breathable membrane, and leave it to stand for 30 minutes under the infrared lamp to complete the air electrode treatment. In this embodiment, the thickness of the waterproof breathable membrane is 0.2 mm, and the porosity of the waterproof breathable membrane is 20%; the current collector is a stainless steel mesh.
[0095] Example 7
[0096] A method for treating an air electrode is a method for treating an air electrode using an air electrode catalyst prepared by the method for preparing an air electrode catalyst in Example 2, comprising the following steps:
[0097] 1) Preparation of catalyst ink: air electrode catalyst and Ketjen black are placed in a container, and ultrapure water, anhydrous ethanol and Nafion solution are added, and then ultrasonically dispersed in an ultrasonic cleaning machine for 50 minutes to prepare catalyst ink; in this embodiment, the mass volume ratio of air electrode catalyst, conductive carbon black, water, anhydrous ethanol and Nafion solution is 3 mg: 1 mg: 450 μL: 450 μL: 40 μL;
[0098] 2) Forming a catalyst layer on the current collector: Under irradiation with an infrared lamp at 75°C, drop catalyst ink onto the current collector that has been meshed with a waterproof breathable membrane, and let it stand for 20 minutes under the infrared lamp to complete the air electrode treatment. In this embodiment, the thickness of the waterproof breathable membrane is 0.1 mm, and the porosity of the waterproof breathable membrane is 15%; the current collector is nickel foam.
[0099] Example 8
[0100] A method for treating an air electrode is a method for treating an air electrode using an air electrode catalyst prepared by the method for preparing an air electrode catalyst in Example 3, comprising the following steps:
[0101] 1) Preparation of catalyst ink: air electrode catalyst and Ketjen black are placed in a container, and ultrapure water, anhydrous ethanol and Nafion solution are added, and then ultrasonically dispersed in an ultrasonic cleaning machine for 70 minutes to prepare catalyst ink; in this embodiment, the mass volume ratio of air electrode catalyst, conductive carbon black, water, anhydrous ethanol and Nafion solution is 4 mg: 2 mg: 500 μL: 500 μL: 60 μL;
[0102] 2) Forming a catalyst layer on the current collector: Under irradiation with an infrared lamp at 85°C, drop catalyst ink onto the current collector that has been meshed with a waterproof breathable membrane, and leave it to stand for 40 minutes under the infrared lamp to complete the air electrode treatment. In this embodiment, the thickness of the waterproof breathable membrane is 0.3 mm, and the porosity of the waterproof breathable membrane is 30%; the current collector is carbon paper.
[0103] Example 9
[0104] A method for treating an air electrode is a method for treating an air electrode using an air electrode catalyst prepared by the method for preparing an air electrode catalyst in Example 4, comprising the following steps:
[0105] 1) Preparation of catalyst ink: air electrode catalyst and Ketjen black are placed in a container, and ultrapure water, anhydrous ethanol and Nafion solution are added, and then ultrasonically dispersed in an ultrasonic cleaning machine for 55 minutes to prepare catalyst ink; in this embodiment, the mass volume ratio of air electrode catalyst, conductive carbon black, water, anhydrous ethanol and Nafion solution is 3.2 mg: 1.2 mg: 460 μL: 460 μL: 45 μL;
[0106] 2) Forming a catalyst layer on the current collector: Under irradiation with an infrared lamp at 78°C, drop catalyst ink onto the current collector that has been meshed with a waterproof breathable membrane, and leave it to stand for 25 minutes under the infrared lamp to complete the air electrode treatment. In this embodiment, the thickness of the waterproof breathable membrane is 0.2 mm, and the porosity of the waterproof breathable membrane is 18%; the current collector is carbon cloth.
[0107] Example 10
[0108] A method for treating an air electrode is a method for treating an air electrode using an air electrode catalyst prepared by the method for preparing an air electrode catalyst in Example 5, comprising the following steps:
[0109] 1) Preparation of catalyst ink: air electrode catalyst and Ketjen black are placed in a container, and ultrapure water, anhydrous ethanol and Nafion solution are added, and then ultrasonically dispersed in an ultrasonic cleaning machine for 65 minutes to prepare catalyst ink; in this embodiment, the mass volume ratio of air electrode catalyst, conductive carbon black, water, anhydrous ethanol and Nafion solution is 3.8 mg: 1.7 mg: 490 μL: 490 μL: 55 μL;
[0110] 2) Forming a catalyst layer on the current collector: Under irradiation with an infrared lamp at 83°C, the catalyst ink is dripped onto the current collector that has been meshed with the waterproof breathable membrane, and the air electrode treatment is completed after standing under the infrared lamp for 35 minutes. In this embodiment, the thickness of the waterproof breathable membrane is 0.15 mm, and the porosity of the waterproof breathable membrane is 25%; the current collector is a stainless steel mesh.
[0111] Embodiment 11
[0112] A zinc-air battery device comprises at least one battery cell, wherein the battery cell comprises a zinc electrode and an air electrode treated by any one of the air electrode treatment methods of Embodiments 6 to 10.
[0113] Example 12
[0114] A zinc-air battery device, such as Fig.12 and 13 As shown, a battery cell is included, and the battery cell includes a zinc electrode 1 and an air electrode 2 treated by an air electrode treatment method of Example 6.
[0115] In this embodiment, the battery unit further includes an electrode plate 3, a fixed ventilation plate 4, and a fixed pressure plate 5; wherein the zinc electrode 1 and the air electrode 2 are arranged opposite to each other, the electrode plate 3 is arranged between the zinc electrode 1 and the air electrode 2, the fixed ventilation plate 4 is arranged on the other side of the air electrode 2, and the fixed pressure plate 5 is arranged on the other side of the zinc electrode 1. In this embodiment, the electrode plate 3 is provided with an electrolyte tank 31, in which an electrolyte is arranged; the electrode plate 3 is also provided with an electrolyte injection port 32 connected to the electrolyte tank 31. The electrolyte is an alkaline electrolyte, mainly a potassium hydroxide solution or a sodium hydroxide solution, or a hydrogel of a potassium hydroxide solution and polyvinyl alcohol.
[0116] In this embodiment, the air electrode 2 is composed of a current collector 21, an air diffusion layer 22 and a catalyst layer 23, wherein the air diffusion layer 22 is arranged on one side of the current collector 21, and the catalyst layer 23 is arranged on the other side of the current collector 21. The current collector 21 is one of stainless steel mesh, nickel foam, carbon paper or carbon cloth.
[0117] In this embodiment, an air inlet 41 penetrating the fixed ventilation plate 4 is provided in the middle of the fixed ventilation plate 4. The gas diffusion layer 22 can be seen through the air inlet 41. In this embodiment, the gas diffusion layer 22 is a waterproof breathable membrane.
[0118] In this embodiment, a gasket 6 is provided between the air electrode 2 and the electrode plate 3, and between the zinc electrode 1 and the electrode plate 3; the gasket 6 can enhance the sealing between the air electrode 2 and the electrode plate 3, and between the zinc electrode 1 and the electrode plate 3, thereby improving the stability of the connection between the zinc electrode 1, the air electrode 2, the electrode plate 3, the fixed ventilation plate 4 and the fixed pressure plate 5. The gasket 6 is made of PTFE, which has the properties of low impedance, high gas barrier, high temperature resistance and corrosion resistance.
[0119] In this embodiment, bolt holes 7 are opened at the four corners of the electrode plate 3, the fixed ventilation plate 4 and the fixed pressure plate 5. The electrode plate 3, the fixed ventilation plate 4 and the fixed pressure plate 5 are tightly fixed and arranged by bolts, which has the advantages of easy installation and avoiding leakage.
[0120] In this embodiment, the electrode plate 3, the fixed ventilation plate 4 and the fixed pressure plate 5 are all organic glass plates.
[0121] Embodiment 13
[0122] A zinc-air battery device, such as Fig.14 As shown, three battery cells are included, and the three battery cells are closely arranged and fixed by bolts. Each battery cell includes a zinc electrode 1 and an air electrode 2 treated by an air electrode treatment method of Example 6.
[0123] Comparative Example 1
[0124] A method for preparing an air electrode catalyst. The difference between this comparative example and Example 1 is that in the thermal decomposition reaction of this comparative example, the temperature is raised to 800° C. for thermal decomposition reaction for 2 hours, and the remaining components and preparation method are the same as those in Example 1.
[0125] The air electrode catalyst prepared in this comparative example 1 is recorded as FeCo@NC-800.
[0126] Comparative Example 2
[0127] A method for preparing an air electrode catalyst. The difference between this comparative example and Example 1 is that in the thermal decomposition reaction of this comparative example, the temperature is raised to 1000° C. for thermal decomposition reaction for 2 hours, and the remaining components and preparation method are the same as those in Example 1.
[0128] The air electrode catalyst prepared in this comparative example 2 is recorded as FeCo@NC-1000.
[0129] Comparative Example 3
[0130] A method for preparing an air electrode catalyst. The difference between this comparative example and Example 1 is that in the preparation of the aerogel precursor in step S2 of Comparative Example 3, Co(NO3)2·6H2O and Fe(NO3)3·9H2O are not added to the mixed aqueous solution used for soaking the alkali-treated loofah, and the remaining preparation steps and preparation conditions are the same as those in Example 1.
[0131] The air electrode catalyst prepared in this comparative example 3 is denoted as NC.
[0132] Comparative Example 4
[0133] A method for preparing an air electrode catalyst. The difference between this comparative example and Example 1 is that in the preparation of the aerogel precursor in step S2 of Comparative Example 4, Co(NO3)2·6H2O is not added to the mixed aqueous solution used for soaking the alkali-treated loofah, and the remaining preparation steps and preparation conditions are the same as those in Example 1.
[0134] The air electrode catalyst prepared in this comparative column 4 is denoted as Fe@NC.
[0135] Comparative Example 5
[0136] A method for preparing an air electrode catalyst. The difference between this comparative example and Example 1 is that in the preparation of the aerogel precursor in step S2 of Comparative Example 5, Fe(NO3)3·9H2O is not added to the mixed aqueous solution used for soaking the alkali-treated loofah, and the remaining preparation steps and preparation conditions are the same as those in Example 1.
[0137] The air electrode catalyst prepared in this comparative column 5 is denoted as Co@NC.
[0138] Comparative Example 6
[0139] A zinc-air battery device. The difference between this comparative example and Example 12 is that a commercial precious metal Pt / C-RuO2 catalyst is used instead of the air electrode catalyst of the present invention to treat the air electrode.
[0140] Structural morphology characterization
[0141] (I) Morphological characterization by transmission electron microscopy
[0142] The air electrode catalyst (FeCo@NC-900) prepared by the preparation method of an air electrode catalyst in Example 1 was characterized by transmission electron microscopy (TEM). Figure 1 , Figure 3 and Figure 4 shown.
[0143] In addition, the FeCo@NC-900 prepared in Example 1 was characterized by high-resolution transmission electron microscopy (H-TEM). Figure 2 shown.
[0144] Depend on Figures 1 to 4 It can be seen that the morphology and crystal phase of the FeCo@NC-900 catalyst were observed using TEM technology. From the figure, it can be seen that a large number of metal particles are dispersed on the carbon sheet, and the average size of the particles is 29.80nm. Figure 2 It can be seen that the metal particles are wrapped in the carbon shell, not isolated and dispersed on the carbon substrate. H-TEM is used to further determine the composition and structure of the material. Figure 3 and Figure 4 It can be clearly seen that the interplanar spacing of 0.201nm and 0.364nm corresponds to the FeCo (111) crystal plane and the graphite carbon (002) crystal plane, respectively, which further confirms the formation of FeCo nanoparticles and is coated with a graphitized carbon layer with a thickness of about 1.75nm. The graphitized carbon layer can not only effectively protect the dissolution and agglomeration of metal particles under strong alkaline conditions, but also improve the stability of the material. In addition, the close contact between graphite carbon and metal particles is beneficial to the interfacial charge transfer, thereby improving the electrocatalytic performance.
[0145] (II) Particle size distribution detection
[0146] The air electrode catalyst prepared by the preparation method of an air electrode catalyst in Example 1 was tested for particle size distribution. The test results are as follows: Figure 5 As shown. Figure 5 It can be seen that the particle size of FeCo@NC-900 prepared in Example 1 is mainly distributed between 15nm and 45nm, among which the particle size between 25nm and 30nm accounts for the largest proportion, reaching about 20%.
[0147] (III) Structural characterization by X-ray powder diffraction
[0148] The air electrode catalyst (FeCo@NC-900) prepared by the preparation method of an air electrode catalyst in Example 1 was characterized by X-ray powder diffraction. Figure 6 As shown. Figure 6It can be seen that there is an obvious and broad characteristic peak at 2θ≈26.0°, which corresponds to the (002) crystal plane of graphite carbon (standard card number JCPDF#00-041-1487). This indicates that the crystal structure of graphite carbon exists in the FeCo@NC-900 sample. Graphite carbon has excellent electrical and thermal conductivity and is widely used in catalysts, batteries and other fields. Figure 6 It can be observed that the FeCo@NC-900 catalyst shows three obvious characteristic peaks, which are located at 24.0°, 65.4° and 82.9°, respectively. These peaks correspond to the (110), (200) and (211) crystal planes of the FeCo alloy (standard card number JCPDF#03-065-4131).
[0149] Performance Testing
[0150] (I) Activity detection of oxygen reduction reaction (ORR) at different thermal decomposition temperatures
[0151] The air electrode catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested for ORR activity. Figure 7 As shown. Figure 7 It can be seen that the FeCo@NC-900 of Example 1 shows an excellent half-wave potential of 0.81 V and a limiting current density of 5.56 mA cm during the ORR process. -2 , which is better than the FeCo@NC-800 in Comparative Example 1 (0.79 V, 5.65 mA cm -2 ) and FeCo@NC-1000 of Comparative Example 2 (0.79 V, 5.06 mA cm -2 ).
[0152] (II) Activity detection of oxygen evolution reaction (OER) at different thermal decomposition temperatures
[0153] The air electrode catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested for OER activity. Figure 8 shown.
[0154] Among them, the overpotential is the evaluation standard of OER activity. Generally, the lower the overpotential, the better the OER activity. Figure 8 It can be seen that the FeCo@NC-900 of Example 1 only needs an overpotential of 349 mV to drive 10 mA cm -2 The current density is better than that of FeCo@NC-800 (366V) in Comparative Example 1 and FeCo@NC-1000 (357V) in Comparative Example 2.
[0155] (III) Activity test of blank group, single metal and bimetallic catalysts for oxygen reduction reaction (ORR)
[0156] The air electrode catalysts prepared in Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were respectively tested for ORR activity. Fig. 9 shown.
[0157] Depend on Fig. 9 It can be seen that at the same thermal decomposition temperature, the ORR activity of FeCo@NC-900 in Example 1 is better than that of NC in Comparative Example 3 (0.44 V, 2.92 mA cm -2 ), Fe@NC of Comparative Example 4 (0.69 V, 3.62 mA cm -2 ) and Co@NC of Comparative Example 5 (0.79 V, 4.41 mA cm -2 ).
[0158] (IV) Activity testing of blank group, monometallic and bimetallic catalysts for oxygen evolution reaction (OER)
[0159] The air electrode catalysts prepared in Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were tested for OER activity. Fig.10 shown. Fig.10 In the figure, the OER activity detection curves of sample NC and sample Fe@NC are almost identical.
[0160] Depend on Fig.10 It can be seen that at the same thermal decomposition temperature, for OER activity, the FeCo@NC-900 of Example 1 only needs an overpotential of 349 mV to drive 10 mA cm -2 The current density is better than that of NC (556V) in comparative example 3, Fe@NC (551V) in comparative example 4 and Co@NC (450V) in comparative example 5.
[0161] (V) Charge and discharge cycle performance test of zinc-air battery
[0162] The zinc-air battery devices of Example 12 and Comparative Example 6 were subjected to constant current charge and discharge tests to detect the charge and discharge cycle performance. The test results are as follows: Fig.11 shown.
[0163] Depend on Fig.11 It can be seen that the air electrode of the zinc-air battery device of Example 11 uses the FeCo@NC-900 catalyst prepared in Example 1, so that the zinc-air battery device can -2The current density of NC-900 was stably cycled for 300 hours. However, under the same test conditions, the air electrode of the zinc-air battery device of Comparative Example 6 applied a commercial precious metal Pt / C-RuO2 catalyst, and its discharge voltage was significantly decayed after about 70 hours, and it failed quickly after running for 141 hours. Therefore, it is shown that the catalytic electrode of FeCo@NC-900 prepared by the present invention has excellent long-cycle performance in the zinc-air battery device.
[0164] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing an air electrode catalyst, characterized in that: The following steps are involved: S1, alkali treatment of loofah: dispersing the loofah in an alkali solution, then heating it for hydrothermal reaction, vacuum filtering, washing and drying to obtain an alkali-treated loofah; S2. Preparation of an aerogel precursor: soaking the alkali-treated loofah in a mixed aqueous solution containing cobalt ions, iron ions and urea, stirring and freeze-drying the mixture to obtain an aerogel precursor; S3, thermal decomposition reaction: subjecting the aerogel precursor to thermal decomposition reaction under a protective atmosphere to obtain the air electrode catalyst.
2. The method for preparing an air electrode catalyst according to claim 1, characterized in that: In the step S1, the loofah is dispersed in an alkaline solution, and then heated to 140° C.-160° C. for hydrothermal reaction for 10 h-14 h, and then vacuum filtered, washed with deionized water until neutral, and placed in a vacuum drying oven at 50° C.-70° C. for drying for 10 h-20 h to obtain an alkali-treated loofah; and / or The alkaline solution is one or both of potassium hydroxide and sodium hydroxide; the molar concentration of the alkaline solution is 2M-4M; and / or The mass ratio of the loofah to the alkaline solution is 1:(8-12).
3. The method for preparing an air electrode catalyst according to claim 1, characterized in that: In the step S2, the alkali-treated loofah is immersed in a mixed aqueous solution containing Co(NO3)2·6H2O, Fe(NO3)3·9H2O and urea, and magnetically stirred for 50 min-70 min, and then freeze-dried with liquid nitrogen for 45 h-50 h to obtain an aerogel precursor; and / or The molar concentrations of the cobalt ions and the iron ions are both 0.05mM-0.15mM, the molar concentration of the urea is 1M-1.5M, and the mass ratio of the alkali-treated loofah to the mixed aqueous solution is 1:(45-55).
4. The method for preparing an air electrode catalyst according to claim 1, characterized in that: In the step S3, the aerogel precursor is placed in a tubular furnace, heated to 850°C-950°C at a heating rate of 4°C / min-6°C / min in an argon atmosphere, and subjected to thermal decomposition reaction for 1.5h-2.5h to obtain the air electrode catalyst.
5. An air electrode catalyst, characterized in that The air electrode catalyst is prepared by the preparation method of any one of claims 1 to 4.
6. An air electrode treatment method, characterized in that: A method for treating an air electrode using an air electrode catalyst prepared by the method for preparing an air electrode catalyst according to any one of claims 1 to 4, comprising the following steps: 1) Preparation of catalyst ink: placing the air electrode catalyst and conductive carbon black in a container, adding water, anhydrous ethanol and Nafion solution, and then performing ultrasonic dispersion to prepare catalyst ink; 2) Forming a catalyst layer on the current collector: under the irradiation of an infrared lamp, the catalyst ink is dripped onto the current collector that has been meshed with the air diffusion layer, and after the current collector is left to stand under the infrared lamp, the air electrode treatment is completed.
7. An air electrode treatment method according to claim 6, characterized in that: In the preparation steps of the catalyst ink, the mass volume ratio of the air electrode catalyst, conductive carbon black, water, anhydrous ethanol and Nafion solution is (3-4) mg: (1-2) mg: (450-500) μL: (450-500) μL: (40-60) μL; and / or, the conductive carbon black is Ketjen black; and / or, the water is ultrapure water; and / or, the ultrasonic dispersion is ultrasonically dispersed in an ultrasonic cleaning machine for 50 min-70 min.
8. An air electrode treatment method according to claim 6, characterized in that: In the step of forming the catalyst layer on the current collector, the catalyst ink is dripped onto the current collector having meshed with the waterproof breathable membrane under the irradiation of an infrared lamp at 75° C. to 85° C., and the air electrode treatment is completed after the current collector is left to stand under the infrared lamp for 20 min to 40 min; and / or The air diffusion layer is a waterproof breathable membrane; and / or the thickness of the waterproof breathable membrane is 0.1 mm-0.3 mm, and the porosity of the waterproof breathable membrane is 15%-30%; and / or The current collector is one of stainless steel mesh, nickel foam, carbon paper or carbon cloth.
9. A zinc-air battery device comprising at least one battery cell, characterized in that: The battery cell comprises a zinc electrode and an air electrode treated by an air electrode treatment method according to any one of claims 6 to 8.
10. A zinc-air battery device as claimed in claim 9, wherein the battery unit further comprises an electrode plate, a fixed ventilation plate, and a fixed pressure plate; The zinc electrode and the air electrode are arranged opposite to each other, the electrode plate is arranged between the zinc electrode and the air electrode, the fixed ventilation plate is arranged on the other side of the air electrode, and the fixed pressure plate is arranged on the other side of the zinc electrode; The electrode plate is provided with an electrolyte tank, in which an electrolyte is provided; An air inlet penetrating through the fixed ventilation plate is provided in the middle of the fixed ventilation plate; and / or Gaskets are arranged between the air electrode and the electrode plate, and between the zinc electrode and the electrode plate.
Citation Information
Patent Citations
Porous carbon loaded transition metal composite material as well as preparation method and application thereof
CN115566205A
High-energy-density sealed metal-air battery and battery pack thereof
CN116666842A